The loud silence of Francine Green [compact disc, unabridged] - Cushman, Karen (Listening Library, 2006)
In 1949, thirteen-year-old Francine goes to Catholic school in Los Angeles where she becomes best friends with a girl who questions authority and is frequently punished by the nuns, causing Francine to question her own values.